2018
DOI: 10.1307/mmj/1538705132
|View full text |Cite
|
Sign up to set email alerts
|

Families of Elliptic Curves in P3 and Bridgeland Stability

Abstract: We study wall crossings in Bridgeland stability for the Hilbert scheme of elliptic quartic curves in three dimensional projective space. We provide a geometric description of each of the moduli spaces we encounter, including when the second component of this Hilbert scheme appears. Along the way, we prove that the principal component of this Hilbert scheme is a double blow up with smooth centers of a Grassmannian, exhibiting a completely different proof of this known result by Avritzer and Vainsencher. This de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…This unique wall leads to a classification of all semistable sheaves, and the description of the moduli spaces follows. The special case uses techniques close to what was done for some Hilbert schemes of curves in [32] and [11].…”
Section: Ingredientsmentioning
confidence: 99%
See 1 more Smart Citation
“…This unique wall leads to a classification of all semistable sheaves, and the description of the moduli spaces follows. The special case uses techniques close to what was done for some Hilbert schemes of curves in [32] and [11].…”
Section: Ingredientsmentioning
confidence: 99%
“…In [29] Okonek and Spindler proved the same bounds for all semistable sheaves of rank two. Moreover, they described the moduli space if either c = 0 and d ≤ −6 or c = −1 and d ≤ − 11 2 . The above theorem fills in all the remaining special cases.…”
Section: Introductionmentioning
confidence: 99%
“…Chen [4] proved that the component corresponding to the twisted cubics is the flip of M 0,0 (P 3 , 3) over the Chow variety. Avritzer and Vainsencher [2] proved that the component corresponding to elliptic quartics in Hilb 4t P 3 is smooth and isomorphic to a double blow up of Gr(1, 9); Gallardo, Huerta and Schmidt [13] computed its effective cone. Chen, Coskun and Nollet [5] showed that the component corresponding to a pair of codimension two linear spaces meeting transversely is smooth and isomorphic to a blow of Sym 2 Gr(n − 2, n).…”
Section: Introductionmentioning
confidence: 99%
“…Even when the wall-crossing does not yield the entire MMP, we can still recover crucial information about the birational geometry of the moduli spaces from it, especially when we are able to identify one of them with know projective varieties such as Gieseker moduli spaces. Problems in this sense have been studied for example in [Sch15] and [GLHS16] for the moduli spaces of ideal sheaves of twisted cubics and elliptic quartic curves on P 3 .…”
Section: Introductionmentioning
confidence: 99%